Log Loading with Cable-puller - Asthana, M. N.; Sethi, Y. R. (Indian Forester, 1964)
A method to employ ’Greif’ cable-puller for loading of logs into truck has been described. It has been shown that the cost of loading by this method is much lower than by hand loading. Moreover, the cost is actually less for bigger logs than for smaller logs.